The Effect of Remuneration on Employee Performance at PT. BNI Syariah Bintaro Branch Office - Andy Nugroho; Moh. Sutoro (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of remuneration on employee performance at PT. BNI Syariah Bintaro Branch Office. The method used is explanatory research with a sample of 45 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study Remuneration variable obtained an average score of 3.773 with good criteria. Employee performance variable obtained an average score of 3.898 with good criteria. Remuneration has a positive and significant effect on employee performance with the regression equation Y = 10.035 + 0.826X, and the correlation coefficient value is 0.826 or has a strong relationship with a determination value of 68.2%. Hypothesis test obtained sig. 0.000 < 0.05